2018
DOI: 10.1155/2018/7352735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on the Outcomes of Assisted Reproductive Technology: An Overview of Systematic Reviews

Abstract: Objectives To conclude the evidence from systematic reviews (SRs) and meta-analyses assessing the effectiveness of acupuncture to treat couples with subfertility undergoing ART. Methods We searched the major databases from their inception to March 2018: PubMed, Embase, The Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, Chongqing VIP, and Sino-Med (the Chinese database). The primary outcomes of the overview were live birth and clinical pregnancy, and secondary outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…While a significant proportion of these potency-inducing supplements such as animal products and herbal plants may have similar phosphodiesterase type 5 inhibitor (PDE5i) substrates, there is no strong scientific evidence supporting their use in males with ED and MI [ 77 ]. The data for Chinese herbal medications, acupuncture, mind-body practice, and faith-based healing are sparse or inconclusive regarding positive effects on male fertility [ 80 81 82 ]. These confounding data can be partially attributed to the unproven large commercial amounts of supplements advertised to improve sperm quality, the difficulty in controlling various modifiable factors, generally sub-optimal quality, and the heterogeneous nature of the evidence as well as the question of whether any of these therapies translates in improving the chances of conception and live births or increasing miscarriage risk.…”
Section: Management Strategies For Various Sexual Dysfunctions In Mal...mentioning
confidence: 99%
“…While a significant proportion of these potency-inducing supplements such as animal products and herbal plants may have similar phosphodiesterase type 5 inhibitor (PDE5i) substrates, there is no strong scientific evidence supporting their use in males with ED and MI [ 77 ]. The data for Chinese herbal medications, acupuncture, mind-body practice, and faith-based healing are sparse or inconclusive regarding positive effects on male fertility [ 80 81 82 ]. These confounding data can be partially attributed to the unproven large commercial amounts of supplements advertised to improve sperm quality, the difficulty in controlling various modifiable factors, generally sub-optimal quality, and the heterogeneous nature of the evidence as well as the question of whether any of these therapies translates in improving the chances of conception and live births or increasing miscarriage risk.…”
Section: Management Strategies For Various Sexual Dysfunctions In Mal...mentioning
confidence: 99%
“…Another systematic review had a similar result with a series of clinical trials that included a total 44,619 participants (of whom 6344 participants received acupuncture treatment) in 210 primary studies in 2018 on acupuncture-assisted IVF. 9 However, the reported cases did not indicate if the inclusion criteria allowed conditions specifically requiring IVF, such as tubal blockage.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the lack of high-quality evidence from systematic reviews (SRs) on acupuncture, the recommendations for acupuncture in the guidelines are not high in strength [2]. Several studies have shown that a high risk of bias (RoB) was the main reason for rating down the quality of evidence [3][4][5], and the conclusion cannot be trusted if randomized controlled trials (RCTs) were rated as high RoB [6]. Additionally, one methodological study has shown that supplementary information from trialists can significantly increase the rate of trials at low RoB rather than high RoB by reducing the rate of unclear RoB [7].…”
Section: Introductionmentioning
confidence: 99%